2022
DOI: 10.3390/antibiotics11080984
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Pyrrolopyrimidines with Low MIC on Staphylococcus aureus and Synergistic Effects with an Antimicrobial Peptide

Abstract: Currently, there is a world-wide rise in antibiotic resistance causing burdens to individuals and public healthcare systems. At the same time drug development is lagging behind. Therefore, finding new ways of treating bacterial infections either by identifying new agents or combinations of drugs is of utmost importance. Additionally, if combination therapy is based on agents with different modes of action, resistance is less likely to develop. The synthesis of 21 fused pyrimidines and a structure-activity rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…To produce 6‐aryl‐4‐benzyl‐7 H ‐pyrrolo[2,3‐ d ]pyrimidines for biological studies, the dihalogenated building block 35 was synthesized following a previously reported procedure (Scheme 4). [20] The C‐6 position could be chemoselectively arylated by Suzuki–Miyaura cross‐coupling conditions giving 36 . Negishi cross‐coupling on pyrrolopyrimidine 36 was performed using a selection of substituted benzyl bromides with Pd(PPh 3 ) 4 as catalyst in THF at 60 °C (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…To produce 6‐aryl‐4‐benzyl‐7 H ‐pyrrolo[2,3‐ d ]pyrimidines for biological studies, the dihalogenated building block 35 was synthesized following a previously reported procedure (Scheme 4). [20] The C‐6 position could be chemoselectively arylated by Suzuki–Miyaura cross‐coupling conditions giving 36 . Negishi cross‐coupling on pyrrolopyrimidine 36 was performed using a selection of substituted benzyl bromides with Pd(PPh 3 ) 4 as catalyst in THF at 60 °C (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…A putative Tmk inhibitor called JK-274 ( Figure 2A ) was previously found to have a low MIC (20 μM, 8 μg/mL) toward S. aureus . When combined with a ½ MIC BTP-001 (2 μM, 8 μg/mL), the MIC for JK-274 was reduced 8-fold ( Olsen et al, 2022 ). In this study, we wanted to investigate the molecular basis of the individual and combined effects of JK-274 and BTP-001 by using signalomics supplemented with metabolomics.…”
Section: Resultsmentioning
confidence: 99%
“…All concentrations are given as net peptide concentrations and 4 μg/mL equals approximately 1 μM. The halogenated pyrrolopyrimidine JK-274 (( R )-4-(4-((1-(4-bromophenyl)ethyl)amino) - 7 H- pyrrolo[ 2,3-d ]pyrimidin-6-yl)phenol) was synthesized as previously described and 4 μg/mL is approximately equal to 10 μM ( Olsen et al, 2022 ). JK-274 was dissolved in DMSO and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations